Perancangan SOP Bahan Baku dan Kualitas Produk Pastry Section di The Westlake Resort Yogyakarta - Adesty Lasally; Mirna Diansyah (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Based on the researcher’s observations at The Westlake Resort Yogyakarta, particularly in the Food and Beverage Product Department within the Pastry Section, several issues and challenges were identified, namely the absence of a clearly established Standard Operating Procedure (SOP). It was therefore concluded that the SOP in the Pastry Section at The Westlake Resort Yogyakarta has not been properly designed or implemented. In order to determine in detail the design of the SOP to be applied in the Pastry Section, a study was conducted under the title “Designing Standard Operating Procedures (SOP) for Raw Materials and Product Quality: A Case Study of the Pastry Section at The Westlake Resort Yogyakarta.” The research employed a qualitative method with a descriptive approach. Sampling was carried out using purposive sampling with a non-probability technique, while data collection techniques included observation and interviews. Data analysis was conducted through four stages: data collection, data reduction, data presentation, and conclusion drawing. The results of the data analysis indicated that the SOP in the Pastry Section at The Westlake Resort Yogyakarta had not yet been established, and the proposed SOP design had not been fully implemented, nor did it meet the job description indicators of the pastry section as outlined by Suhardjito (2006), particularly in terms of raw materials and product quality. The study concludes that although the staff in the Pastry Section at The Westlake Resort Yogyakarta have SOPs in place, they do not fully comply with the specified indicators. Certain aspects, such as product quality and workplace hygiene, have not been consistently applied, thereby necessitating an evaluation and the formal establishment of SOPs.